Factores motivacionales que influyen en la participacion de las socias en la organizacion de base del pueblo joven el bosque - distrito trujillo - en el año 2014 - Gambini Cerna, Judith Violeta (2014)
The research is descriptive in nature; in which was applied as primary inductive deductive methods, qualitative research techniques as observation and interview and quantitative technique has been used to survey; the objective was to describe and analyze the motivational factors influencing participation of members in the grassroots organization of young people Forest, Trujillo district. The sample universe was confirmed by 35 women equivalent to 100% of the members of the grassroots organization of young people the Forest. The results highlight that social and personal factors directly influence the operation of the grassroots organization. Finally, given the findings of the research and recommendations are made based on experience and knowledge gained during the study to achieve a barrier active participation of women in all spheres, seeking involvement in the transformation of a society with equal rights.